Measuring the Total-Factor Green Efficiency in China’s Industrial Sectors: A Parametric Approach - Zhenghuan Wang (Discrete Dynamics in Nature and Society)
At present, China’s industrial economy is facing a severe problem of green transformation, so the measurement of total-factor green efficiency has become one of the research hot spots. Combining Shephard’s distance function and metafrontier model, this study constructs a parametric total-factor green efficiency model in consideration of technology heterogeneity. Stochastic metafrontier analysis, which controls individual effects, is used to estimate metafrontier green efficiency. This study calculates the green efficiency of Chinese industrial sectors. Results show that there are significant differences in metafrontier green efficiency between high- and low-emission groups, and the efficiency level of the low-emission group is systematically higher than that of the high-emission group. Compared with pooled green efficiency and existing studies without considering technology heterogeneity, the metafrontier green efficiency is more intuitive and realistic. In order to achieve green industrial growth, this study suggests that the government should implement heterogeneous energy conservation and emission reduction policies for high- and low-emission groups, especially to encourage carbon-intensive industries to improve the use of existing group technologies, and to promote technology diffusion and spillover between high- and low-emission groups. Based on the reliable measurement of green efficiency, green productivity might be reliably explored as well in the future.